Nonlinear Signal Response in Electrospray Mass Spectrometry: Implications for Quantitation of Arsenobetaine Using Stable Isotope Labeling by Liquid Chromatography and Electrospray Orbitrap Mass Spectrometry - Ouerdane, Laurent; Meija, Juris; Bakirdere, Sezgin; Yang, Lu; Mester, Zoltan (AMER CHEMICAL SOC, 2012)
Isotope amount ratio measurements by electrospray ionization. mass spectrometry show large systematic biases. Moreover, the signal ratio response can vary nonlinearly with respect to the amount ratio depending on the concentration of the analyte or coeluting matrix components, among other things. Since isotope dilution relies inherently on the linearity of response, accurate quantitation is then more difficult to achieve. In this study, we outline a method to eliminate the quantitation errors due to the effects of the nonlinear signal response. The proposed approach is a hybrid of the method of standard additions and isotope dilution allowing correction for nonlinear trend. As a proof of concept, determination of arsenobetaine content in fish tissue was performed using liquid chromatography coupled with a linear quadrupole ion trap (LTQ) Orbitrap mass spectrometer. The nonlinear isotope dilution method could, in principle, be applied to correct isotope ratio measurement biases in popular relative quantitation methods of biomolecules such as stable isotope labeling by amino acids in cell culture (SILAC), isotope-coded affinity tag (ICAT), or isobaric tags for relative and absolute quantification (iTRAQ).
Keywords: CALIBRATION CURVES; ACCURATE MASS; IDENTIFICATIONS; IONS; Chemistry